HEALTH OF THE WORKER AND HUMAN RIGHTS: THEORETICAL AND CONCEPTUAL ANALYSIS IN PUBLIC ENVIRONMENTS - Carvalho, Sandra; Haonat, Angela Issa; Caúla, Bleine Queiroz (Seven Editora, 2025)
This article discusses workers' health and human rights through a theoretical and conceptual analysis in public settings. Based on the 1988 Federal Constitution and international fundamental rights treaties, the study recognizes health as an essential social right and a duty of the State. Therefore, the research question was: How do theoretical and normative foundations support workers' health as a human right in public work settings, especially in light of evidence of institutional illness? The overall objective was to provide a theoretical and conceptual analysis of workers' health as an expression of human rights in public settings, exploring its legal, social, and environmental foundations. Based on a literature review, the study examines the main factors of workplace illness in the public sector, highlighting absenteeism as an indicator of job insecurity. It concludes that consolidating workers' health as a human right requires institutional commitment and a cultural shift in public management.DOI: https://doi.org/10.56238/sevened2025.037-007